Orchitis: An unusual presentation of polyarteritis nodosa - Nelofar Islam; Debanjali Sinha; Parasar Ghosh; Chhanda Datta; Uttara Chatterjee (Wolters Kluwer Medknow Publications, 2018)
Polyarteritis nodosa (PAN), a systemic necrotizing vasculitis with multiorgan development, is generally restricted to the medium-sized muscular arteries. The varied initial clinical presentations of PAN can lead to a delayed diagnosis. We present the case of a middle-aged male patient who presented with an acute onset right-sided testicular pain as the initial clinical symptom with ischemic changes on ultrasonogram, thereby requiring orchiectomy. This was reported to be a case of tubercular epididymo-orchitis. On review, the biopsy revealed features of necrotizing arteritis as seen in PAN with fibrinoid necrosis and giant cells, thus highlighting the fact that vasculitis due to PAN may have a localized presentation at the time of diagnosis. PAN should be distinguished from other causes of epididymo-orchitis and other vasculitis lesions, the most common being tubercular etiology in the Asian population.